AIRPORT CONCESSIONS IN BRAZIL AND ITS INFLUENCES ON SERVICE QUALITY: THE CASES OF BRASÍLIA AND SÃO PAULO – GUARULHOS AIRPORTS - Allis, Thiago; Castro, Rafael; Carla Fraga, Carla Fraga (Journal of Tourism, Sustainability and Well-being, 2017)
Over the last decade, the Brazilian air market has tripled in size, a result of economic expansion and the spread of the air travel culture, among others. As far as airport infrastructures are concerned, during the mega-events era (2014 FIFA World Cup and the 2016 Summer Olympics), the airport management sector started to receive greater investments from private and foreign companies. After 2012, a large array of improvements took place, in order to meet the demands associated with the mega-events, but also to tackle the increase of domestic air traffic. In this context, this paper aims to identify, describe and analyze the influences of the airport concession in Brazil on the quality of services perceived by the users (passengers). For that, an analysis of the reports of the aviation authorities is carried out. The airports of Guarulhos (São Paulo) and Brasília (Federal District), among the first to be privatized, were selected as case studies. From this study, the mobility of global capital associated with airport management deserves to be highlighted, while the expertise of these large companies is expected to contribute to the increase in the quality of services in Brazilian airports - historically managed by public sector.